Immunoblot Analysis and Comparative IgE Responses of Atopic Patients to Extracts of the Domestic Mite Blomia tropicalis - Montealegre, Federico; Goth, Kerstin; Hart, Barbara (Puerto Rico Health Sciences Journal, 2009)
Background. The domestic mite Blomia tropicalis is found in subtropical and tropical environments, and its clinical importance as a sensitizing agent in allergic disease is widely accepted. Objective. To investigate the IgE reactivity to allergens present in extracts of the domestic mite B. tropicalis, and compare the IgE responses to these allergens by asthmatics, patients with atopic dermatitis and allergic rhinitis, as well as nonatopic controls. Methods. Extracts from B. tropicalis were used for skin tests. The B. tropicalis specific IgE in the serum were measured using the FAST Plus Test and immunoblot analysis. Results. A total of 199 volunteers participated in the study. The data show that 18 out of 29 polypeptide bands present in extracts of this mite species were recognized by the allergic and control sera. Of these allergens, four showed a high IgE binding frequency and had relative molecular weights of 104, 80, 68 and 14 kDa. The 14 kDa allergen demonstrated the highest IgE binding frequency. Conclusion. Sera from atopic patients reacted to more allergens than sera from patients controls. Extracts from pure bodies of B. tropicalis contain one immunodominant and three important allergens. A common characteristic between all of the sera tested was the high degree of serum IgE reactivity observed to the 14 kDa allergen.